Aerobics health as means of increasing somatic health of students of special medical group - Pivneva M.M; Rumba O.G (Kharkov National Pedagogical University, 2013)
We prove the feasibility of employment by improving aerobic low intensity (LowImpact - heart rate in the range 128-140 beats / min, or 60-74% of HR max) with students of special medical groups with disabilities cardiovascular system. The choice of three varieties of improving aerobics - classical, dance, tap dance - and with the help of laboratory experiment investigated the specificity of their effects on the physical health of students. According to the results of laboratory studies developed two versions of the author's method of application for improving aerobic physical education classes with students with disabilities but cardiac-vascular system, the main difference between them lies in the relationship and the manner of the classical sequence of exercises, dance, step aerobics. By comparing the results of educational experiments proved that both variants techniques contribute significantly improved key indicators of physical health subjects and thus are fairly equal in the nature of exposure.